2019
DOI: 10.1097/pgp.0000000000000653
|View full text |Cite
|
Sign up to set email alerts
|

PNL2: A Useful Adjunct Biomarker to HMB45 in the Diagnosis of Uterine Perivascular Epithelioid Cell Tumor (PEComa)

Abstract: Perivascular epithelioid cell tumors (PEComa) are rare neoplasms characterized by co-expression of melanocytic and muscle markers. HMB45 and Melan-A are used to confirm a PEComa diagnosis; however, both are often focally expressed and sensitivity for Melan-A is low. PNL2 is a reliable biomarker for epithelioid melanoma and renal angiomyolipoma/PEComa. The objective of this study was to determine PNL2 utility in diagnosing uterine PEComas as well as distinguishing PEComas from uterine smooth muscle tumors (SMTs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 27 publications
1
19
1
Order By: Relevance
“…However, cathepsin K expression has also been described in SMTs, 17,59,107 albeit usually not diffuse, but highlights that this marker also is not specific for PEComas. Likewise, PNL2 may also rarely be focally positive (< 10%) in uterine SMTs, but results are limited to a single series of 45 tumors 59 …”
Section: Differential Diagnosismentioning
confidence: 99%
See 4 more Smart Citations
“…However, cathepsin K expression has also been described in SMTs, 17,59,107 albeit usually not diffuse, but highlights that this marker also is not specific for PEComas. Likewise, PNL2 may also rarely be focally positive (< 10%) in uterine SMTs, but results are limited to a single series of 45 tumors 59 …”
Section: Differential Diagnosismentioning
confidence: 99%
“…PEComas are characterized by expression of myomelanocytic markers (Figure 3A,B; Table 1), but the extent and intensity of staining required for their diagnosis remains controversial. Among large studies HMB‐45 is expressed in 99% of all PEComas 17,23,40,41,59 ; however, the extent of staining is highly variable. In two studies, only 13% (1/8 and 2/16, respectively) of tumors showed >25% staining 23,40 while in a third series, 28/32 (88%) 17 reached this threshold.…”
Section: Clinicopathologic Featuresmentioning
confidence: 99%
See 3 more Smart Citations